Going out for a walk: Empathizing with streets through their façades in Lima - Ramírez, Miguel Córdova (2022)
Walking down a street is not the same as going out for a walk. One of the differences is that by going out for a walk it is possible to empathize with the city façades. Through a qualitative and comparative analysis of the perceptions and urban imaginaries of young adults, we propose to analyze how they understand walking through the different streets of the Lima neighborhoods of Lince, Jesús María, and Santa Beatriz, which are experiencing physical changes in their streets due to the expansion of the real estate market. It was revealed that the disposition to empathize with façades was related to an idea of life that was used as a differentiating factor, and which included attributes of location, visibility, variety, sense of community, and historicization. Therefore, when there was greater disposition to empathize with the streets, walking acquired a new character and people did go out for a walk.